Incorporation of reduced glutathione to the extender improves frozen-thawed sperm function and fertility potential in mandarin fish (Siniperca chuatsi) - Sen Yang; Wenjie Xu; Yanglin Hua; Qingxin Ruan; Zining Meng (Aquaculture Reports)
Semen cryopreservation is a valuable tool for assisted reproduction in aquatic species. Despite the various advantages in hatchery practices, damage occurred during the process of freezing and thawing can result in compromised sperm quality. Supplementation of antioxidant in the freezing medium is suggested to be an effective strategy against cryodamage. Therefore, the objective of this study was to investigate the potential effects of reduced glutathione (GSH) on post-thaw sperm quality and fertility in mandarin fish (Siniperca chuatsi). Semen was diluted with freezing medium at a ratio of 1:6 (v/v), with GSH supplemented at different concentrations (0, 1, 2, 4, 8 mM) and then subjected to cryopreservation. Sperm motion parameters, viability, mitochondrial activity, lipid peroxidation, and apoptosis were assessed after thawing. The addition of GSH at 4 mM presented significantly higher (P < 0.05) post-thaw sperm total motility (%, 71.7 ± 7.2 vs. 64.6 ± 2.2), progressive motility (%, 14.9 ± 2.8 vs. 10.7 ± 0.4), curvilinear velocity (μm/s, 59.6 ± 4.5 vs. 51.2 ± 0.9), straight line velocity (μm/s, 25.3 ± 2.4 vs 22.1 ± 0.5), and average path velocity (μm/s, 37.3 ± 3.6 vs. 32.7 ± 0.6), compared to the control group. Viability was higher (P < 0.05) in sample supplemented with 2 mM GSH (82.0 ± 5.4 %) compared to other groups. In addition, GSH-supplemented samples showed significantly higher mitochondrial activity and a lower level of apoptosis (P < 0.05) compared to the control. Regarding lipid peroxidation, the rate was lower in treatments supplemented with GSH, although not significant (P > 0.05). After artificial insemination, a higher fertilization rate was recorded with GSH at concentrations of 2 and 4 mM (P < 0.05). Moreover, a significantly higher hatching rate (P < 0.05) was observed in the 2 mM GSH-treated group. In conclusion, the addition of GSH seems to provide a cryoprotective effect for mandarin fish sperm, resulting in improved post-thaw sperm quality and fertilizing capacity.